Bridging the gap: enhancing science communication in synthetic biology with specific teaching modules, school laboratories, performance and theater - Schmitt, Franz-Josef; Golüke, Marie; Budisa, Nediljko (Frontiers in Synthetic Biology, 2024)
Synthetic biology, an interdisciplinary field merging biology, engineering, and computer science, holds significant promise but also gives rise to ethical and safety issues and concerns. Effective communication of scientific concepts is essential to bridge the gap between the scientific community and the general public. Here we present four communication strategies from our own experience that could help address this gap: (i) the teaching module “iGEM-Synthetic Biology”: Students at Technische Universität Berlin (TU Berlin) engage in synthetic biology projects, showcasing their work in a competition format that includes the creation of videos and websites. (ii) Long Night of the Sciences: Students and supervisors from the international Genetically Engineered Machine (iGEM) module at TU Berlin share their results with presentations, experiments, and quiz games during this public event. (iii) Theatre play: Festival für Freunde e.V. has developed a play titled “Life from the Toolbox” to explain genetic modification and synthetic biology for the audience. The play incorporates readings and educational videos. (iv) Heinz-Bethge-Foundation electron microscopy school lab: This laboratory utilizes hands-on experiments with microscopes, including electron microscopes, to visually explain intricate scientific concepts in physics, biology, and synthetic biology. It encourages high school students to delve deeper into the realm of science. These four initiatives represent a communication strategy that resonates with diverse audiences and is suitable to cover the public as a target group independent from their prior knowledge of the scientific background.